2022
DOI: 10.1021/acs.orglett.1c03900
|View full text |Cite
|
Sign up to set email alerts
|

Increased Antiaromaticity through Pentalene Connection in [n]Cyclo-1,5-dibenzopentalenes

Abstract: Conjugated nanohoops incorporating nonalternant hydrocarbons have altered optoelectronic properties compared to [n]cycloparaphenylenes or other purely aromatic hoops. We synthesized [n]cyclo-1,5-dibenzopentalenes (n = 4, 5), in which nonalternant dibenzo[a,e]pentalenes are connected through their pentalene units. This leads to an increase in antiaromatic character and low-lying LUMO energies. Calculations show puckered or entangled conformations of the precursor macrocyclic Pt-complexes. Our study proves diben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
(72 reference statements)
1
24
0
Order By: Relevance
“…In the structurally related indeno[1,2-b]fluorenes, transient absorption spectroscopy measurements showed that the excited-state lifetimes were shorter than the timescale at which fluorescence is usually observed. 84 We also did not observe fluorescence for those hoops, in which the -system is dominated by DBPs, namely [n]CDBPs 2 and 3, 16 [n]C-5,10-DBPs 4 and 5, 18 51 On the other hand, in [2]DBP [12]CPP 6 13 and DBP[n]CPPs 8 and 9, 17 which consist of DBPs alternating with [6]-or [7]paraphenylene linker(s), we were able to detect fluorescence, albeit of low intensity. This fluorescence stemmed from the paraphenylene units, which explains the similar wavelengths and shapes of the emission bands, with maxima at 471 nm (6), 487 nm (8), and 479 nm (9), corresponding to a bathochromic shift with increasing strain (the spectra of 8 and 9 are shown in Figure 8B).…”
Section: Electronic Propertiesmentioning
confidence: 70%
See 4 more Smart Citations
“…In the structurally related indeno[1,2-b]fluorenes, transient absorption spectroscopy measurements showed that the excited-state lifetimes were shorter than the timescale at which fluorescence is usually observed. 84 We also did not observe fluorescence for those hoops, in which the -system is dominated by DBPs, namely [n]CDBPs 2 and 3, 16 [n]C-5,10-DBPs 4 and 5, 18 51 On the other hand, in [2]DBP [12]CPP 6 13 and DBP[n]CPPs 8 and 9, 17 which consist of DBPs alternating with [6]-or [7]paraphenylene linker(s), we were able to detect fluorescence, albeit of low intensity. This fluorescence stemmed from the paraphenylene units, which explains the similar wavelengths and shapes of the emission bands, with maxima at 471 nm (6), 487 nm (8), and 479 nm (9), corresponding to a bathochromic shift with increasing strain (the spectra of 8 and 9 are shown in Figure 8B).…”
Section: Electronic Propertiesmentioning
confidence: 70%
“…We also accessed [ n ]C-1,5-DBPs 4 and 5 connected through the 5- and 10-positions of the five-membered DBP rings to compare the two conjugation pathways (Scheme 1 B). 18 As described above, the use of boronic ester 14 in the Pt-mediated cyclization led to success and allowed us to isolate tetrameric 4 and pentameric 5 . At 0.8 and 1.9%, respectively, the yields were lower than those of the [ n ]CDBPs 2 and 3 , probably due to the lower solubility of the intermediate Pt complexes.…”
Section: Synthesis Of Dbp-based Nanohoopsmentioning
confidence: 93%
See 3 more Smart Citations